Pengaruh Pemberlakuan Program SPP Gratis 12 Tahun Terhadap Perekonomian Indonesia - Putri Balqis; Jeny Olivia Ivolina Purba; Dian Amelia Putri (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This research aims to find out the views of the public regarding the issue of the implementation of free 12-year tuition fees (Sumbangan Pembinaan Pendidikan) from elementary, junior high, to high school levels in the Riau Islands. The sources of this research were obtained from students and university students located in Tanjungpinang. This type of research uses a qualitative approach. This research uses primary data. Primary data used in this study were obtained directly through distributing questionnaires to respondents. This study involved 32 people, including students and students in Tanjungpinang City. One of the factors that cause a weak educational foundation is the low level of income and the large population in Indonesia. Analyzing the quality of education is very important before schools receive assistance or mentoring, and this issue is not only related to money. It was found that communication between policymakers and implementers can change how programs are run.